Archaeology and Economic Development - Hana Koriech; Colin Sterling (Papers from the Institute of Archaeology, 2013)
Conference Review: Archaeology and Economic Development, UCL Institute of Archaeology, 21-22 September 2012.
Keywords: economics; development